COVID-19 pandemic and cardiovascular mortality and morbidity in the Czech Republic. (3rd October 2022) - Bruthans, J; Rychtarikova, J; Jarkovsky, J
Abstract: Background: During 2020–2021 the Czech Republic was hit by several waves of COVID-19 epidemic. 1, 700, 000 acquired the disease and in 39, 000 this was the main cause of death, making the Czech Republic one of the most affected countries. But there was also a considerable increase in CV (cardiovascular) mortality. Due to repeated lockdowns and further restrictions the CV medical care was restricted. Purpose: To learn about the impact of covid pandemics on CV health we performed further analyses. Methods: We analysed the 2019–2021 data of CV mortality, CV hospital and outpatient treatments and data on risk profiles of CV patients. The analysis was based on the Czech Mortality and Hospitalization Register and Health Insurance Register (data about health care provided) from the Institute for Health Information and Statistics of the Czech Republic. Results: The total CV mortality 2019–2021, after years of declining CV mortality, increased from 47, 393 in 2019 to 51, 299 in 2021 (8.24%), slightly less in women than in men. The mortality from acute coronary syndrome (ACS, I20–I24) decreased from 4287 to 4182 (2.45%), mortality for chronic CHD (I25) increased from 18, 049 to 19, 216 (6.47%), for pulmonary embolism (I26) from 824 to 867 (5.2%), for sudden cardiac death and heart arrest from 1143 to 1276 (increase 11.6%). Mortality for heart failure (I50) increased from 5477 to 6728 (22.8%), for stroke (I60-I64) did not change: from 5406 to 5426 (+0.4%), for arterial hypertension increased from 3923 to 4822 (22.9%). There was a shift from inhospital to outhospital CV mortality. Hospital admissions for ACS declined by 40% to recover to former numbers in the second half of 2021. In the outpatient CV care there was a decrease in clinical and laboratory investigations. Based on data from the Czech AH excellence centers of the ESH, with the first lockdown the number of patients attending centers decreased by 90% to recover nearly to previous numbers with lifted restrictions and to decrease less with further waves of epidemics. The patients continued drug treatment and home BP measurements. The laboratory controls of hyperlipidaemias and of diabetes were affected in similar way, the impact on blood pressure, lipid and diabetes control needs further analyses. There was increase in prevalence of obesity and substantial decrease in physical activities. Conclusions: In changing CV mortality, not only morbidity and mortality caused by direct deleterious effect of covid infection on CV system (injury to heart muscle, thromboembolic complications, arrhytmias, etc), but also "colateral damage", caused by compromised CV medical care and prevention should be considered. The most striking increase in mortality we found in heart failure and arterial hypertension, obviously conditions in need of close medical follow up. Only full restitution of complex CV treatment and prevention will restore positive trends in CV morbidity and mortality. Funding Acknowledgement: Type of funding sources: None.